Definition and severity grading of postoperative lymphatic leakage following inguinal lymph node dissection - Gerken, Andreas; Herrle, Florian; Jakob, Jens; Weiß, Christel; Rahbari, Nuh Nabi; Nowak, Kai; Karthein, Constantin; Hohenberger, Peter; Weitz, Jürgen; Reißfelder, Christoph; Dobroschke, Jakob Christian (Langenbeck's archives of surgery, 2020)
Lymphatic complications occur frequently after radical inguinal lymph node dissection (RILND). The incidence of lymphatic leakage varies considerably among different studies due to the lack of a consistent definition. The aim of the present study is to propose a standardized definition and grading of different types of lymphatic leakage after groin dissection.